Safeguards and Sustainability Policies in a Changing World : An Independent Evaluation of World Bank Group Experience - Independent Evaluation Group (Washington, DC: World Bank, 2012)
The World Bank Group's (WBG) safeguards and sustainability policies were put in place to prevent or mitigate adverse impacts of its projects on people and the environment. These goals remain critical given current environmental and social trends. Recent global experience in the financial and environmental arenas demonstrates clearly the need to put in place and enforce regulatory frameworks that balance costs and benefits, both private and social. This evaluation looks, for the first time, at the full set of safeguards and sustainability policies used in the WBG including the World Bank, the International Finance Corporation (IFC), and the Multilateral Investment Guarantee Agency (MIGA). The findings are intended to inform ongoing reviews of policies and strategies across the WBG, with an eye toward greater effectiveness in achieving environmental and social outcomes.